Reduced Prefrontal Activation During the Tower of London and Verbal Fluency Task in Patients With Bipolar Depression: A Multi-Channel NIRS Study - Fu, Linyan; Xiang, Dan; Xiao, Jiawei; Yao, Lihua; Wang, Ying; Xiao, Ling; Wang, Huiling; Wang, Gaohua; Liu, Zhongchun (Frontiers in Psychiatry, 2018)
Background: The Tower of London (TOL) task is one of the most commonly used tests for evaluating executive functions, and can indicate planning and problem-solving abilities. The aim of this study was to evaluate hemodynamic changes in patients with bipolar depression during the TOL task and the verbal fluency task (VFT) using near-infrared spectroscopy. Methods: Forty-three patients with bipolar depression and 32 healthy controls (HCs) matched for sex, age, handedness, and years of education were enrolled in this study. Changes in oxygenated and deoxygenated hemoglobin (oxy-Hb and deoxy-Hb) levels in frontal areas during the TOL task and VFT were evaluated using a 41-channel NIRS system. Results: During the TOL task, the patients with bipolar depression had lower activation levels in the bilateral dorsal-lateral prefrontal cortex (DLPFC) than the HCs. During the VFT task, the patients with bipolar depression had lower activation levels in the right ventrolateral prefrontal cortex (VLPFC), the right DLPFC and both the right and left prefrontal cortex (PFC) than the HCs. Limitations: Our sample size was small, and the effects of medication cannot be excluded. Conclusions: These results indicate that planning and problem solving dysfunction is related to the impairment of the prefrontal cortex in patients with bipolar depression, and NIRS can be used to assess planning and problem solving abilities, which are essential to daily life in patients with bipolar disorder.